THE AUTHORITY OF VILLAGE CREDIT UNION AS THE SUBJECT OF LIABILITY RIGHTS - Wairocana, I Gusti Ngurah; Sumerthayasa, Putu Gede Arya; Ratmaningrum, Jeanne Wiryandani (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 1 No 2 (2016), 2016)
According to the Bali Provincial Regulation No. 8 concerning Village Credit Union (hereinafter referred to as LPD) Article 2 paragraph (1) states that: LPD is a village-owned financial union conducting business in the village and for the benefit of the villagers. This is confirmed by the presence of the Decision of the Third Big Meeting by Village Assembly (MDP) Bali No. 009 / SK-PA III / MDP Bali /Vffl /2014 Article I paragraph (1), namely, the Village Credit Union is one of the possessions of the village. This type of research used in this thesis is a normative study. Normative study is the one that examines the level of legal norms, finding the non-existence of the LPD status as a legal subject of liability rights, so there is a legal vacuum in which the status of the LPD as the subject of a liability rights is not stipulated in the legislation and these problems will be a legal discovery. LPD is the possession of the village, so LPD cannot be the legal subject of liability right because the village itself has not been the subject of law. So the security liability agreement made by LPD is invalid because it does not qualify his legitimate agreements written in Article 1320 paragraph (4) of Civil Code regarding lawful cause or legal cause.
Keywords: LPD, Legal Subject, Liability Rights